The tolerance of wheat (Triticum aestivum L.) to Septori tritici blotch - Collin, François (2018)
The Septoria tritici blotch disease (STB, pathogen Zymoseptoria tritici) is the most damaging foliar infection of wheat crops in Europe. Disease management strategies include cultivar resistance, disease escape strategy and fungicides. However, these strategies have failed to provide a complete protection of wheat crops.